ICL Postimplantation Decentration and Tilt in Myopic Patients with Primary Iridociliary Cysts. (16th January 2023) - Wang, Ying; Yang, Ruibo; Huang, Yue; Zhang, Chen; Liu, Hui; Jia, Zhe; Zhao, Shaozhen
Abstract : Purpose . To observe the decentration and tilt of implantable collamer lens (ICL) as well as possible visual effects postimplantation in primary iridociliary cysts. Methods . The present investigation was a retrospective cohort study. All 48 patients (91 eyes) who underwent ICL surgery at the Center of Refraction Surgery of Tianjin Medical University Eye Hospital between July 2018 and May 2020 were split into two groups based on the absence or presence of primary iridociliary cysts established by ultrasonic biological microscopy (UBM) examination. Intraocular pressure (IOP), corrected distance visual acuity (CDVA), uncorrected distance visual acuity (UDVA), anterior chamber angle (ACA), anterior chamber volume (ACV), and anterior chamber depth (ACD) were recorded preoperatively and postoperatively at 1, 6, and 12 months. Additionally, we performed an analysis of the ICL vault, decentration, and tilt using a rotating Scheimpflug Oculus Pentacam camera system at 1, 6, and 12 months after surgery. Results . No serious complications were observed. Significant postoperative improvement P < 0.05 of UDVA was established in the two studied groups; however, we did not observe statistically significant intergroup differences P > 0.05 throughout the entire research period. In each group, the preoperative ACA, ACV, and ACD were statistically significantly reduced P < 0.05, but no such decrease was established between their postoperative values P > 0.05 . We observed no statistical differences between both groups with regard to their values of IOP, ACA, ACV, ACD, ICL vault, ICL decentration, and tilt at 1, 6, and 12 months after surgery. Similarly, no statistically significant within-group correlation P > 0.05 of the decentration of ICL and the tilt and the CDVA values was established. Conclusion . No postimplantation effect of ICL with a central hole on vision was established in myopia patients with primary iridociliary cysts, within certain limits of ICL decentration and tilt values.